Managers’ Knowledge about basic Management Concepts in Telecommunication Industry - Shah, Aisha Bashir; Phulpoto, Lutuf Ali; Shaikh, Faiz Muhammad (Journal of Asian Business Strategy, 2012)
The study was conducted to see the managerial skills and knowledge of all first line managers working in cellular companies like Mobilink, Telenor and Warid etc. The purpose of this study is to highlight the significance of the requirement of basic and essential managerial skills like conceptual, human & technical for a manager especially in this high and intense competition between different mobile operators. A complementary survey was conducted from 5 main offices of all cellular companies in Sukkur city. A five point likert scale was used as a measurement tool. SPSS statistical software was used for data analysis. Results showed that about 85% managers working as 1st line manager do have good knowledge of Management role and skills. Data was collected via questionnaires and direct interviews.